Voluntary Corporate Climate Initiatives and Regulatory Loom: Batten Down the Hatches - Dragan Ilić; Janick Christian Mollet (University of Basel, Center of Business and Economics (WWZ), 2015)
The rationale of voluntary corporate initiatives is often explained with preparedness for future regulation. We test this hypothesis for the Chicago Climate Exchange (CCX) and the Climate Leaders (CL), two popular voluntary US environmental programs to curb carbon emission that were operating during a decisive regulatory event. In 2009 the Waxman-Markey Bill surprisingly passed the House of Representatives and brought the US economy on the brink of a nationwide CO2 emission trading system. In an event study we assess how the stock market adjusted prices when the likelihood of CO2 regulation suddenly increased. Our results suggest that only membership in the CCX was considered beneficial, an initiative whose design happened to dovetail with the bill. Earlier membership announcement effects paint a complementary picture. But membership alone cannot account for the entire price adjustments. Our results reveal that a substantial part of the market reaction consisted of industry-wide effects.
Keywords: G38; Q53; Q54; Q58; 330; Voluntary markets; permit markets; climate change; greenhouse gas emissions; CO2; corporate social responsibility; shareholder wealth